Phytochemical Studies of Taxus Species and Their Uses in Cancer Treatment - Subedi, Thaneshwar (Janapriya Journal of Interdisciplinary Studies, 2018)
Cancer occurs when cell division runs amok. Cancer is a mass of abnormal, unhealthy cells that are dividing and growing in an uncontrolled way. Cancerous cells with oncogene and damaged deoxyribo nuclic acid (DNA) neither repair nor die. Chemical carcinogens, ionizing radiations, viral or bacterial infection, hormonal change, heredity etc are the main cancer causing agents. In this article, treatment of cancer by plant alkaloid, Taxol, is studied by using secondary sources. Cancer can be treated by plant alkaloids; Taxol, vica rosea, colchicine known as anticancer drugs. Paclitaxel binds the protein tubulin in mitotic spindle, suppresses the tubulin-microtubule dynamic equilibrium, kills the DNA damaged defective cells to control abnormal rapid cell division. Paclitaxel (C47H51NO14) has a large number of common, infrequent and rare sideeffects. Its structure was elucidated and published on the basis of H1–NMR spectrum. Janapriya Journal of Interdisciplinary Studies, Vol. 6 (December 2017), Page: 148-159